The distribution of field-induced charges in C60 fullerite - Kuprievich, V.A.; Kapitanchuk, O.L.; Shramko, O.V.; Kudritska, Z.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The profile of injected charges in a C60-based field-effect transistor (FET) is considered. A simple scheme for calculations of the charge distribution between the 2D layers of C60 molecules is founded on a small magnitude of the interball electron hopping. Analytical solutions of the equations for the charge distributions are obtained in the limits of thick and thin crystals. The charge density is shown to drop exponentially with the crystal depth. The calculations predict the relativepart of induced charges involved in the surface layer to be 3/4 and 2/3 in the cases of electron and hole injection, respectively.